(3GdfbV Ydi UGMH eLehY GdeMjW ajeG NGda ajg GdRjOjIs - (3CHh GdaVd LYaQ Hf CMeO Hf YHO GdSdGe Hf CHi jMjis
(3ChdgG (B:s
(3EYde Cf UGMH GdcJGH ChQO ef GdcdGe ai CHhGH GdEeGeI aUhdkG ef GdfU Ydi hefgG eG EMJL Hg dCSHGH EeGeI ef CHj HcQ hYeQ hYKeGf s
(3BNQgG (B:s
(3hceG dh YQafG ef WHjH GdfUjMI ddeQVi Ke TGgOfGg jaYd Hge ef bWY hbdY hZjQ Pdc s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds